Exploring the way to improve communication practices within section III, Human Resource Management Division Chief Minister's Department : an action learning approach - Sharifah Alauyah, Bte. Syed Muhammad Shibli. (1998)
This project employed the Action Learning approach in exploring the way to improve communication practices within Section ill, Human Resource Management Division, Chief Minister' s Department, Kuching, Sarawak. By its statement of vision, Section ill aspires to be the most efficient, innovation and proactive arm of the Chief Minister's Department, providing fast and quality service to the government and their customeJK'The Section is serving not only the external customer -civil servants from the other ministries, government departments, government agencies or statutory bodies as well as members of the public, but also those working in the organisation itself, i.e. other sections of the Human Resource Division. Based on the preliminary observation done, it was identified that the communication practices within the Section needs to be improved. The problem of lacking effective communication may lead to the functional incompetence of the Section. With its service-oriented function, the Section must therefore project a very positive image of excellence, efficiency and effectiveness to the whole organisation. It was also justified that an Action Learning approach could be used in this exploratory research project. The method consists of spiral of cycles of planning, action, observation, reflection and evaluation. This project has highlighted a number of processes and characteristics of the Action Learning method that emerged from the meeting, discussions and observations on the Action Research Group members and their learning sets. By exploring the used of Action Learning method to improve communication, the researcher is convinced that this method will be a promising approach to explore. Though the project was limited due to time constraints and some other limiting factors, it was evidenced that the participants involved were convinced that the method can be further introduced to the employees in the entire organisation. The participants also admitted that learning takes time, nevertheless exploring the method should be seen as part of acquiring more knowledge and skills towards bringing changes and improvement and each and everyone in the organisation should get involved. Though the improvement in communication moved in a moderate pace, it should not be seen as a cutting point to judge that the participants involved were not effective in carrying out the Action Learning project. It was unquestionable that the participant'! were trying their very best to explore, learn and use the method to improve communication within the Section. It was also justified that learning took place and the research questions were acceptably answered.